High Prevalence of Virulence Genes in Specific Genotypes of Atypical Enteropathogenic Escherichia coli - Xu, Yanmei; Bai, Xiangning; Jin, Yujuan; Hu, Bin; Wang, Hong; Sun, Hui; Fan, Ruyue; Fu, Shanshan; Xiong, Yanwen (Frontiers in Cellular and Infection Microbiology, 2017)
Atypical enteropathogenic Escherichia coli (aEPEC) strains are emerging enteropathogens that have been detected worldwide. A collection of 228 aEPEC strains (121 from diarrheal patients, 27 from healthy carriers, 47 from animals and 33 from raw meats) were investigated for serotypes, virulence gene profiles and phylogenetic relationships. Sixty-six O serogroups were identified. For the 20 virulence genes detected, statistically significant differences were observed in the overall prevalence of efa1 (lifA), nleB, nleE, set/ent, paa and ehxA genes among strains from diarrheal patients, healthy carriers, animals and raw meats, respectively. Strains from diarrheal patients had significantly higher levels of efa1 (lifA) (29.8% vs. 0, P = 0.0002), nleB (41.3% vs. 7.4%, P = 0.0004), nleE (43.8% vs. 7.4%, P = 0.0002) and set/ent (41.3% vs. 7.4%, P = 0.0004) genes than strains obtained from healthy carriers. The paa gene was identified more often in isolates from raw meats (63.6% vs. 14.8%, P < 0.0001), animals (42.6% vs. 14.8%, P < 0.0122), and diarrheal patients (36.4% vs. 14.8%, P < 0.0225) than in strains obtained from healthy carriers. The ehxA gene was detected more frequently in strains from raw meats than in strains from diarrheal patients (27.3% vs. 2.5%, P = 0.0000) and healthy carriers (27.3% vs. 7.4%, P = 0.0474). The phylogenetic marker, yjaA, was more frequently observed in strains among healthy carriers than in diarrheal patient strains. Among the 228 aEPEC strains, 79 sequence types (STs) were identified. The prominent STs, which comprised strains carrying the four OI-122 genes and lpfA, were ST40, ST328, and ST29. Overall, the results indicate that aEPEC strains isolated in China are highly heterogeneous. aEPEC strains that are potentially more pathogenic appear to be related to specific STs or clonal complexes and serotypes. The high prevalence of diarrhea-associated genes in animal or raw meat strains suggests a zoonotic transmission pathway for potentially human pathogenic aEPEC.